SISTEM PAKAR UNTUK MENDIAGNOSIS HAMA PENYAKIT TANAMAN SEMANGKA MENGGUNAKAN METODE CERTAINTY FACTOR DAN METODE BAYES - Luqman Imam; Henki Bayu Seta; Ria Astriratma (Jurnal Ilmiah Matrik, 2022)
Watermelon is one of the most popular fruits by the general public. Apart from the benefits of watermelon, watermelon also has several diseases that are difficult for farmers to know, such as fruit rot (anthracnose), fruit scabies (bacterial fruit blotch), and others. Although watermelon disease is common, there are still many farmers who do not know about this problem. Therefore, an expert system for watermelon disease detection can be used using the certainty factor algorithm and the Bayes method. Based on the problems that occurred, this study raised the title "Expert System for Diagnosing Pests and Diseases of Watermelon Plants using the Certainty Factor Method and the Bayes Method" to overcome the ignorance of farmers in detecting watermelon disease by entering various characteristics listed in the system based on plant events, the system will provide insight based on existing characteristics using a certainty factor algorithm which will then compare the results with the Bayes method